Evaluation of the frequency of neuroimaging findings in congenital infection by Zika virus and differences between computed tomography and magnetic resonance imaging in the detection of alterations - Bruno Niemeyer de Freitas Ribeiro; Bernardo Carvalho Muniz; Edson Marchiori (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: Congenital infection by the Zika virus (ZIKV) is responsible for severe abnormalities in the development of the central nervous system. The aim of this study was to evaluate and compare the ability of computed tomography (CT) and magnetic resonance (MR) to detect patterns of involvement of the central nervous system in congenital ZIKV syndrome. METHODS: We retrospectively analyzed CT and MR images from 34 patients with congenital ZIKV syndrome and evaluated the differences between the two methods in detecting alterations. RESULTS: The predominant radiographic finding was a simplified gyral pattern, present in 97% of cases. The second most common finding was the presence of calcifications (94.1%), followed by ventriculomegaly (85.3%), dysgenesis of the corpus callosum (85.3%), craniofacial disproportion and redundant scalp (79.4%), complete opercular opening (79.4%), occipital prominence (44.1%), cerebellar hypoplasia (14.7%), and pontine hypoplasia (11.8%). The gyral pattern was extensively simplified in most cases, and calcifications were located predominantly at the cortical-subcortical junction. CT was able to better identify calcifications (94.1% × 88.2%), while MRI presented better spatial resolution for the characterization of gyral pattern (97% × 94.1%) and corpus callosum dysgenesis (85.3% × 79.4%). CONCLUSIONS: Although congenital ZIKV syndrome does not present pathognomonic neuroimaging findings, some aspects, such as calcifications at the cortical-subcortical junction, especially when associated with compatible clinical and laboratory findings, are suggestive of intrauterine ZIKV infection.